Application of artificial intelligence in physical education and future prospects - Yuan Jingjie, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The application of artificial intelligence in physical education is a widely debated topic and has an immense potential for the future. This article discusses the benefits of applying AI to physical education and its possible applications. It is argued that AI can be applied in a number of ways, and it can integrate different types of sensors to collect data. This data can then be used to train an autonomous system which will help the users to make intelligent decisions. Tactical behavior was assessed in subgroups based on team lines (goalkeeper – defenders, defenders – midfielders and midfielders – forward) before and after the intervention in an 8-a-side game. The results suggest that short-term differentiated practice seems insufficient to change linear outcomes, but useful to boost tactical-pattern regularity at subgroup level during the team-possession game phase. Youth-sport academy coaches should employ modified games introducing artificial rules to encourage young players to learn and strengthen the acquisition of regular tactical-patterns